Comparative study of battery energy storage systems in a micro-grid based on real-time simulation - Karim Fellah; Rosa Abbou; Mounir Khiat; Djelloul Rahiel (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The penetration of the distributed energy resources particularly solar and wind power into the electrical system has been increasing, but the intermittent nature of these resources produces perturbations and instability in the electrical grid. Thus, integrating energy storage system into the power grids is one of the best solutions to improve the reliability with performance of electrical systems; ensure power balance and meet consumer demand. Different technologies of energy storage devices have been used to support the integration of renewable energy resources and contribute to improve either the effectiveness with the management of power operating system during critical situations such as power fluctuations in the electrical grid. The main objective of this work is to test the effectiveness of battery energy storage system in reducing active power fluctuations in presence of a perturbation in a micro-grid. In addition, a comparative study is carried out by comparing the response of different battery technologies which are used to support the electrical grid in order to verify the appropriate battery technology for power systems and particularly for energy management in micro-grids during power fluctuations, also, the evaluation of the behaviour, feasibility, performance and effectiveness of BESS is achieved by using real-time simulation.